BIO-ECONOMIC BASIS OF SPATIAL DEVELOPMENT OF THE TERNOPIL REGION (Regional aspects of productive forces development of Ukraine, 2024)
ANNOTATIONIntroduction. The issues of optimizing spatial development of regions through bioeconomicapproaches, which are crucial for solving contemporary global problems, including climate change,depletion of natural resources, and ensuring energy and food security are considered. Traditionalapproaches fail to account for ecological constraints, leading to ecosystem degradation. The integrationof innovative biotechnologies, renewable resources, and environmentally responsible practices in spatialplanning promotes sustainable development of territories, enhances their competitiveness, and preservesnatural wealth. This allows for the creation of new economic growth points, particularly in the agroindustrialcomplex, energy sector, medicine, and bioproduct production, and ensures effective regionalmanagement that balances economic interests with ecological stability.The aim of the article is to investigate the preconditions and prospects of bioeconomy sectordevelopment in the region.Research Methods. The research methodology includes methods of analysis and synthesis, andsystematic generalization.Results. The study analyzes the characteristics and features of the distribution of bioeconomysector objects and bioresource supply in the territory of the Ternopil region. An evaluation of the levels ofdevelopment of different bioeconomy sectors in the region's administrative districts has been conducted.It was found that agriculture, the food industry, especially the sugar and alcohol industries, have thehighest potential for innovation, particularly in waste processing and the production of bioethanol andbiodiesel. It was established that the best development of the bioeconomy sector is realized in theTernopil and Chortkiv districts, requiring intensified work in the Kremenets region. The study concludesthat the overall level of bioeconomy development in the region lags behind neighboring areas. It isemphasized that the implementation of bioenergy technologies has significant ecological benefits,including the reduction of CO2 emissions and the improvement of soil quality, and is crucial for ensuringthe sustainable development of the bioeconomy in the region by expanding organic fertilizer productionand creating favorable conditions for investment. The article proposes directions for further developmentof the bioeconomy sector in the Ternopil region in the future.Keywords: bioeconomy; bioresource; spatial development; region; bioeconomy sector;agriculture.